ChemInform Abstract: Reductive Cyclization of Halo‐Ketones to Form 3‐Hydroxy‐2‐oxindoles via Palladium Catalyzed Hydrogenation: A Hydrogen‐Mediated Grignard Addition. Issue 48 (December 2015) - Shin, Inji; Ramgren, Stephen D.; Krische, Michael J.
Abstract: The reductive cyclization of halodiketones (I) and (III) provides the corresponding oxindole derivatives in moderate to excellent yields.